Tensegrity configuration method for connecting tensegrity units along their axes. (15th February 2017) - Liu, Heping; Geng, Jinsong; Luo, Ani
Abstract: Tensegrity structure is a kind of truss structures which are composed of bars under axial compression and strings under axial tension. It has become a hot spot in the field of sculpture, architecture, aviation and other fields in recent years. A method for building tensegrity structures through connecting tensegrity units is presented and researched systematically here. At first, through analysis for forces of the 3-bar tensegrity structure, the method for adding the components to keep the 3-bar tensegrity unit in equilibrium when changing its rotating angles in the units is researched. The principle for connecting tensegrity units axially follows to be presented. Then the node matrix and connectivity matrix are applied to set up common mathematic models of the tensegrity structures. With the axially-connecting principle and the mathematic models, tensegrity structures with common space shape are set up. Axially-connecting methods for same and different tensegrity units are analyzed. Besides, simulation and physical models are applied to prove that configurations of the obtained tensegrity structures are stable and the axially-connecting method is available. Through research in the paper, a method for configuring the tensegrity structure is summarized systematically, which provides theoretical support for the configuration of more complex structures.